Landasan Filosofis Dinamika Kebijakan Kurikulum Pendidikan Dasar - Frans Samuel; Shely Cathrin (FOUNDASIA, 2025)
This study aims to: (1) identify the philosophical basis behind each basic education curriculum policy, (2) analyse external factors contributing to changes in basic education curriculum policy, and (3) explain the philosophical implications of curriculum policy dynamics on the achievement of national education goals at the basic education level. The identification of problem is related to the instability of philosophical interpretations in the dialectic history of the curriculum, which raises issues regarding the consistency of the philosophical basis of primary education amid the dynamics of regime change. The dominance of global “prejudice” against local policy independence is also highlighted, as well as the gap in application (pedagogy) due to the fragmentation of policy meanings, which creates a paradox at the level of philosophical implications. The primary research data was obtained from policy document/texts, namely Academic Manuscripts and Minister of Education Regulations, which became the corpus of analysis. Secondary data in the form of journals, books, and critical reports were used as historical context and interpretive references. The results of the study clearly map the shift in the dominance of philosophical foundations in basic education curriculum policy, showing the contribution of external factors in influencing changes in basic education curriculum policy, and can provide philosophy-based policy recommendations for policymakers.